Dynamics Modeling and Trajectory Tracking Control of the Mine Rescue Robot with a Variable Structure - Tian Haibo; Lu Maolin; Wang Ao (Jixie chuandong)
A mine rescue robot with variable structure was designed for drilling rescue needs. The robot can change its configuration and enter the downhole environment through drilling. According to the structural characteristics of the robot, the steering mechanism of the robot was analyzed, and a dynamics model describing the steering characteristics of the robot considering the mechanical interaction between the front wheel/track and the soil was established. In order to improve the steering performance of the robot, the transient and steady-state responses of the system were analyzed, and the influence of different structural parameters on the steering performance was analyzed. The structural parameters of the robot were improved. Based on the dynamics model of the robot, a model predictive control （MPC） controller was designed, and trajectory tracking simulations of straight line and circular trajectories were realized. The results show that the established dynamics model is effective, and the MPC trajectory tracking controller can stably track the desired trajectory, laying a foundation for the control of the robot.